2016
DOI: 10.1002/wnan.1404
|View full text |Cite
|
Sign up to set email alerts
|

What is new in nanoparticle‐based photoacoustic imaging?

Abstract: Photoacoustic imaging combines the high temporal and spatial resolution of ultrasound with the good contrast and spectral tuning of optical imaging. Contrast agents are used in photoacoustic imaging to further increase the contrast and specificity of imaging or to image a specific molecular process, e.g., cell-surface proteins or small molecule biomarkers. Nanoparticle-based contrast agents are important tools in photoacoustic imaging because they offer intense and stable signal and can be targeted to specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
104
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(107 citation statements)
references
References 74 publications
(133 reference statements)
1
104
0
Order By: Relevance
“…reported that small nanoparticles are preferable for photothermal therapy because light is mainly adsorbed by the particles and, thus, is efficiently converted into heat for cell and tissue destruction [51]. However, particles smaller than ~10 nm are easily cleared from systemic circulation via the kidneys [52]. Fig 1c shows the absorbance spectra of AXT in saline as a solvent.…”
Section: Resultsmentioning
confidence: 99%
“…reported that small nanoparticles are preferable for photothermal therapy because light is mainly adsorbed by the particles and, thus, is efficiently converted into heat for cell and tissue destruction [51]. However, particles smaller than ~10 nm are easily cleared from systemic circulation via the kidneys [52]. Fig 1c shows the absorbance spectra of AXT in saline as a solvent.…”
Section: Resultsmentioning
confidence: 99%
“…Medical diagnosis and therapeutic options benefit greatly from imaging technologies that combine molecular and microscopic parameters with clinical observations; such a combination is provided by photoacoustic imaging (also known as optoacoustic imaging) . Photoacoustic imaging is a label‐free, non‐ionizing, noninvasive, high‐resolution optical imaging modality that uses optical absorption contrast and ultrasonic resolution . This technology has a high scalability and allows imaging of biological structures, ranging from molecules, organelles, cells, and tissues to entire organs and even entire small animal bodies .…”
Section: Caveats Challenges and Insights On The Diagnosis And Theramentioning
confidence: 99%
“…For example, in photoacoustic imaging ( PAI ), pulses of light excite the contrast agent, which in turn produces a mechanical response, detected as ultrasound [61]. Images are obtained noninvasively, deeper within tissues and with higher spatial resolution compared to purely optical imaging techniques.…”
Section: Imagingmentioning
confidence: 99%